Conversion Filters and Methodological Framework for Sustainable LED Urban Lighting - Listowski, Maciej; Gajewski, Błażej; Bałdyga, Piotr; Szyjka, Sebastian; Stypułkowska, Aneta; Supronowicz, Robert; Fryc, Irena (Photonics Letters of Poland, 2025)
This paper presents comprehensive practical solutions for reducing light pollution in urban LED lighting systems through two complementary approaches: (1) spectral conversion filters for retrofitting existing 4000 K nominal CCT LED luminaires, and (2) systematic methodology for designing environmentally conscious lighting installations. The conversion filter method achieves nominal CCT reduction from 4000 K to CCT ≤ 2700 K, providing a cost effective alternative to complete infrastructure replacement. Full Text: PDF References I. Fryc, S. Bará, M. Aubé, J.C. Barentine, J. Zamorano, "On the Relation between the Astronomical and Visual Photometric Systems in Specifying the Brightness of the Night Sky for Mesopically Adapted Observers", LEUKOS 18, 447 (2022). CrossRef S. Bará, F. Falchi, Artificial light at night: a global disruptor of the night-time environment, Phil. Trans. R. Soc. B 378, 20220352 (2023). CrossRef I. Fryc, The night sky light pollution created by outdoor luminaires, Przegląd Elektrotechniczny 1, 48 (2017). CrossRef J. Falcón, A. Torriglia, D. Attia, F. Viénot, C. Gronfier, F. Behar-Cohen, C. Martinsons, D. Hicks, Exposure to Artificial Light at Night and the Consequences for Flora, Fauna, and Ecosystems, Front. Neurosci. 14, 602796 (2020). CrossRef R. Supronowicz, I. Fryc, Urban park lighting as a source of botanical light pollution, Photon.Lett.PL 11, 90 (2019). CrossRef K.J. Gaston, J. Bennie, T.W. Davies, J. Hopkins, The ecological impacts of nighttime light pollution: a mechanistic appraisal, Biological Reviews 88, 912 (2013). CrossRef T. Longcore, C. Rich, Ecological light pollution, Frontiers in Ecology and the Environment 2, 191 (2004). CrossRef Arrêté du 27 décembre 2018 relatif à la prévention, à la réduction et à la limitation des nuisances lumineuses, (2018). DirectLink Ministère de la Transition Écologique et Solidaire: Bilan de l'application de l'arrêté du 27 décembre 2018 relatif à la prévention, à la réduction et à la limitation des nuisances lumineuses. Paris 2021, (n.d.). DirectLink Generalitat de Catalunya. Decret 190/2015, de 25 d'agost, de desplegament de la Llei 6/2001, de 31 de maig, d'ordenació ambiental de l'enllumenament per a la protecció del medi nocturn. Diari Oficial de la Generalitat de Catalunya, 2015. DirectLink Jefatura del Estado, Ley 31/1988, de 31 de octubre, sobre Protección de la Calidad Astronómica de los Observatorios del Instituto de Astrofísica de Canarias, 1988. DirectLink Joint Research Centre: Revision of the EU Green Public Procurement Criteria for Road Lighting and Traffic Signals. Technical Report, European Commission, 2019. DirctLink CIE TC 5-28, CIE 150:2017 Guide on the Limitation of the Effects of Obtrusive Light from Outdoor Lighting Installations, 2nd Edition, CrossRef CIE TC 4-56, CIE 234:2019 A Guide to Urban Lighting Masterplanning, CrossRef International Dark Sky Community Program Guidelines, (2018). DirectLink A. Machnowska, S. Kołomański, A. Kotarba, T. Ściężor, Zanieczyszczenie światłem w Polsce. Raport 2023, (2023). DirectLink S. Jost, A. Thorseth, T. Poikonen, P. Blattner, T. Gerloff, A. Kokka, P. Dekker, M. Smid, A. Ferrero, T. Kubarsepp, P. Gal, S. Källberg, A. Klej, G. Brida, T. Reiners, K. Ludwig, M. Schneider, L. Hui, EMPIR 15SIB07 PhotoLED - Database of LED product spectra, (2021) CrossRef ANSI C78.377 American National Standard for Electric Lamps-Specifications for the Chromaticity of Solid State Lighting (SSL) Products, (2024). DirectLink A. Hänel, T. Posch, S.J. Ribas, M. Aubé, D. Duriscoe, A. Jechow, Z. Kollath, D.E. Lolkema, C. Moore, N. Schmidt, H. Spoelstra, G. Wuchterl, C.C.M. Kyba, Measuring night sky brightness: methods and challenges, Journal of Quantitative Spectroscopy and Radiative Transfer 205, 278 (2018). CrossRef T. Esposito, K. Houser, Correlated color temperature is not a suitable proxy for the biological potency of light, Sci Rep 12, 20223 (2022). CrossRef M. Pagliaro, Safe and Truly Ecofriendly LED Lighting, Energy Science & Engineering (2025) ese3.70272. CrossRef EN 13201:2015: Road lighting - Part 2: Performance requirements. European Committee for Standardization, Brussels 2015, DirectLink